Peran Pelayanan Penggembalaan untuk Menuntun Pertumbuhan Spiritual Siswa dalam Pendidikan Kristen [The Role of Shepherding Ministry in Directing the Spiritual Growth of Students in Christian Education] - Musa Sinar Tarigan (Diligentia: Journal of Theology and Christian Education, 2021)
Christian education is Christ-centered and guides students to experience spiritual growth to become more Christ like, relate to God, and understand their responsibilities as believers throughout their lives. This ministry of shepherding has very important role because every believer still struggles with sin, and still has the possibility to sin, failing to obey God's will, even though he has not lost his faith in Christ. Christian teachers can guide students in these process of spiritual growth in thinking, feeling, and action (will). This article aims to provide theological foundation on the spiritual growth of believers in the Christian education community through pastoral ministry carried out by teachers. The writing of this article uses descriptive qualitative methods, by examining various phenomena that occur in the context of Christian schools through various relevant literature. The various data were analyzed based on the principles of the Bible as the main source, and literature on theology and other Christian education as secondary resources. The conclusion of this article proves that ministry of shepherding in Christian schools has very significant impact on the process of students' spiritual growth, especially thinking, feeling, and action, to become more Christ like.